Crisis and religious renewal in the Brahmo Samaj, 1860-1884 : a documentary study of the emergence of the "New dispensation" under Keshab Chandra Sen - Damen, Frans L. (Dept. Oriëntalistiek, Katholieke Universiteit Leuven, 1983)
This is a scholarly book mainly concerned with the Brahmo Samaj of India, the sect led by Keshab, which separated from the original Brahmo Samaj, led by Devendranath Tagore, in 1866, and with the New Dispensation sect led by Keshab after the split which emerged in the Brahmo Samaj of India in 1878. The author's interest is in the religious life of these groups rather than in their theology, and he comments that the emphasis of previous writing has been biographical and doctrinal. There is much detailed information about liturgical and devotional changes. These were many: Keshab was ever anxious to gain converts, but the author argues convincingly that the use of Bengali for liturgical purposes and of English for public lectures meant that in northern India the Brahmo Samaj continued to appeal only to the Bengali middle class rather than to local people who spoke Hindi or Panjabi.